Pembentukan Disiplin Belajar Anak SD melalui Rutinitas Kelas Berbasis Reward Non-Material - Fitri Handayani; Bagas Putra; Nanda Putri Ramadhani Putri Ramadhani (FONDASI: Jurnal Pendidikan Dasar, 2026)
This study aims to describe the implementation of non-material reward-based classroom routines in fostering learning discipline in elementary school students, analyze changes in students' learning behavior after implementing this strategy, and identify supporting and inhibiting factors in its implementation. The study used a descriptive qualitative approach with a case study design. The research subjects consisted of elementary school students in one class, the homeroom teacher as the primary informant, and the principal as a supporting informant. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and interactive conclusion drawing. The results show that consistently implemented classroom routines, such as arriving on time, preparing learning materials, following learning procedures, submitting assignments according to schedule, and conducting reflections at the end of the lesson, can foster students' learning discipline habits. Non-material rewards in the form of praise, achievement stickers, star boards, award points, and social recognition have proven effective in increasing students' motivation to adhere to classroom routines. Positive changes were seen in increased punctuality, readiness to learn, compliance with class rules, responsibility for assignments, and student focus during the lesson. Factors supporting the success of this strategy include teacher consistency, clear classroom rules, and a supportive school environment. Meanwhile, obstacles identified include differences in student character, limited learning time, and lack of parental support at home.